2008
DOI: 10.1371/journal.pcbi.1000235
|View full text |Cite
|
Sign up to set email alerts
|

Multistable Decision Switches for Flexible Control of Epigenetic Differentiation

Abstract: It is now recognized that molecular circuits with positive feedback can induce two different gene expression states (bistability) under the very same cellular conditions. Whether, and how, cells make use of the coexistence of a larger number of stable states (multistability) is however largely unknown. Here, we first examine how autoregulation, a common attribute of genetic master regulators, facilitates multistability in two-component circuits. A systematic exploration of these modules' parameter space reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
153
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 61 publications
1
153
0
Order By: Relevance
“…In a recent study (Guantes and Poyatos (2008)) on multistable circuits, the authors found tristable (N = 3) dynamics in genetic circuits of two components involving dimeric regulators. The computational analysis involved a systematic (both deterministic and stochastic) exploration of mutual-activation and mutual-inhibition circuits, i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a recent study (Guantes and Poyatos (2008)) on multistable circuits, the authors found tristable (N = 3) dynamics in genetic circuits of two components involving dimeric regulators. The computational analysis involved a systematic (both deterministic and stochastic) exploration of mutual-activation and mutual-inhibition circuits, i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It involves several regulatory mechanisms including auto-regulation, cross-regulation, binding and unbinding of transcription factors to the promoters, transcriptions, translations, and degradations [7] and takes the form…”
Section: Synergism and Antagonism In A Multistable Decision Modelmentioning
confidence: 99%
“…The model and its simplified form are often used to describe the coexistence of multiple stable states in cell fate decisions [31][32][33]. As shown in [7], strong auto-activation (ρ x 1, ρ y 1) in the model (12)- (13) is necessary for the existence of multiple stable states. The existence of bistable states also needs strong crossactivation (v x 1, v y 1) under which coexistence of more than two stable states is not possible.…”
Section: Synergism and Antagonism In A Multistable Decision Modelmentioning
confidence: 99%
See 2 more Smart Citations